of time. The resulting equation of motion for mass a is
m
d2xa
dt2 =−k(xa −ξ)+k(xb −xa) (4.30)
giving
d2xa
dt2 +
2k m
xa −
k m
xb =
F0 m
cosωt, (4.31)
where F0 = ka. Similarly, the equation of motion for mass b is
d2xb
dt2 −
k m
xa +
2k m
xb = 0. (4.32)
We can solve these two simultaneous equations by, respectively, adding and sub-tracting them. Thus
d2(xa +xb)
dt2 +
k m
(xa +xb) =
F0 m
cosωt (4.33)
and
d2(xa −xb)
dt2 +
3k m
(xa −xb) =
F0 m
cosωt. (4.34)
We now change variables to the normal coordinates
q1 = (xa +xb) and q2 = (xa −xb) (4.35)